Perspektif Suku Dayak Ma'anyan di Desa Majundre terhadap Pendidikan - Eshariyani (Jurnal Ilmiah Kanderang Tingang, 2025)
This study aims to describe and interpret the perspectives of the Dayak Ma’anyan ethnic group regarding the implementation of education. A qualitative approach with a phenomenological design oriented toward theory was employed. The research was conducted in Majundre Village, Central Kalimantan Province, Indonesia. Data collection techniques included participant observation, in-depth interviews, and document analysis. Data analysis involved stages of data condensation, data display, and conclusion drawing and verification. The findings reveal that the Dayak Ma’anyan community views education as: (a) a fundamental need; (b) a means of improving human resources to face global challenges; (c) an opportunity to gain employment; and (d) a vehicle for social transformation.